Clinical and serological prognostic factors in childhood Guillain‐Barré syndrome: A prospective cohort study in Bangladesh. Issue 1 (15th February 2021) - Hasan, Imran; Papri, Nowshin; Hayat, Shoma; Jahan, Israt; Ara, Gulshan; Islam, Badrul; Islam, Zhahirul
Abstract: Guillain‐Barré syndrome (GBS) is the most common cause of acute flaccid paralysis in children. The objective of this study was to investigate the preceding infections, clinical, serological and electrophysiological characteristics and outcome of childhood GBS in Bangladesh. We included 174 patients with GBS aged <18 years from a prospective cohort in Bangladesh between 2010 and 2018. We performed multivariate logistic regression to determine the risk factors for poor outcome. Among 174 children with GBS, 74% (n = 129) were male. Around half of the patients (49%, n = 86) had severe muscle weakness, 65% (n = 113) were bedbound (GBS disability score 4) and 17% (n = 29) patients required mechanical ventilation at admission. Campylobacter jejuni serology and anti‐GM1 IgG antibody were positive in 66% and 21% of the patients respectively. One hundred and forty‐three (82%) patients did not receive standard treatment and half of them recovered fully or with minor deficits at 6‐month. Twenty patients (11%) died throughout the study period. At 3‐month of onset of weakness, complete recovery or recovery with minor deficit was significantly higher in demyelinating GBS patients compared to axonal GBS patients (86% vs 51%, P = .001). Cranial nerve palsy (OR = 4.00, 95%CI = 1.55‐10.30, P = .004) and severe muscle weakness (OR = 0.16, 95%CI = 0.06‐0.45, P = .001) were the important risk factors of poor outcome in children with GBS. Further large‐scale studies are required for better understanding of factors associated with mortality and morbidity in childhood GBS.